Liderança hospitalar: desafios entre o cuidado e a gestão na enfermagem - Prigol, Adrieli Carla (2026)
This study aims to understand the challenges faced by nurses in hospital leadership positions at different management levels and how these challenges relate to the care provided to patients in large hospitals. Throughout history, the nursing profession has been characterized by the union between patient care and administrative management, which requires leaders to possess diverse skills to balance administrative responsibilities and humanized care. This research adopts a qualitative approach with a multiple case study design. Data collection techniques included online forms using the Multifactor Leadership Questionnaire (MLQ) and semi-structured interviews, ensuring data triangulation. The findings indicate that the main challenges faced by nurses in leadership positions include excessive workload, staff and resource shortages, process fragmentation, communication difficulties between different generations, and lack of institutional support. These circumstances intensify stress, weaken the decision-making process, and affect the quality of care and patient safety. Leadership practices characterized by empathy, active listening, and conflict mediation were also highlighted, functioning as ways to cope with the pressures of the organizational environment. The analysis revealed that hospital leadership is permeated by contradictions, as, despite requiring autonomy and quick decisions, it also lacks institutional support and formal platforms for training and reflection. It is concluded that the challenges faced in nursing leadership are both structural and relational, demanding the implementation of policies that value the work, offer emotional support, and promote continuous training, aiming at harmonization between management, the team, and safe patient care.